A General Class of Derivative Free Optimal Root Finding Methods Based on Rational Interpolation. (28th January 2015) - Zafar, Fiza; Yasmin, Nusrat; Akram, Saima; Junjua, Moin-ud-Din
Abstract : We construct a new general class of derivative free n -point iterative methods of optimal order of convergence 2 n - 1 using rational interpolant. The special cases of this class are obtained. These methods do not need Newton's iterate in the first step of their iterative schemes. Numerical computations are presented to show that the new methods are efficient and can be seen as better alternates.